Efecto inhibitorio del aceite esencial de Minthostachys mollis (Kunth) Griseb “muña” sobre Trichophyton mentagrophytes, Microsporum canis y Epidermophyton floccosum - Marquina Bazán, Robert Anthony (2020)
The present research work aims to determine the inhibitory effect of the essential oil of Minthostachys mollis (Kunth) Griseb “muña” on Trichophyton mentagrophytes, Microsporum canis and Epidermophyton floccosum. Healthy plants were collected from the center of Incahuasi, Ferreñafe Province, Lambayeque Region. Whole leaves were collected which were washed with sterile distilled water, disinfected in 2% sodium hypochlorite and dried at room temperature. The essential oil was obtained by means of the steam distillation method. Pure fungal cultures were provided by the Cajamarca Regional Public Health Reference Laboratory. The inhibitory effect was evaluated using the well diffusion method under a completely randomized design. The essential oil dilutions were prepared with tween in the concentrations of 10, 25, 50 and 75 uL, a positive control with 1% terbinafine and a negative control with distilled water, each with three repetitions; The percentage of inhibition, analysis of variance and the tukey test were also determined. The results obtained showed the highest percentage of inhibition in the concentration of 75ul, T. mentagrophytes obtained 69.25%, M. canis 60.47% and E. floccosum was 59.51% .With significant differences with the different treatments.